The Effect of Intergovernmental Transfers and Regional Expenditure on the Financial Performance of Local Governments in the Regencies and Municipalities of North Sumatra Province - Ulfa Utari; Zulhilmi (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to examine the effect of Intergovernmental Transfers and Regional Expenditure on the financial performance of local governments in the regencies and municipalities of North Sumatra Province. The research was conducted to provide empirical evidence regarding the role of transfer funds and regional spending in improving local government financial performance. A quantitative approach was employed using a population of 33 regencies and municipalities in North Sumatra Province 2021–2024 period. A saturated sampling technique was applied, in which all members of the population were selected as the research sample. The data were analyzed using panel data regression with the assistance of SPSS software. The findings indicate that Intergovernmental Transfers and Regional Expenditure simultaneously have a significant effect on the financial performance of local governments in the regencies and municipalities of North Sumatra Province. Furthermore, partial testing reveals that both Intergovernmental Transfers and Regional Expenditure have a positive and statistically significant effect on local government financial performance. These findings suggest that effective management of intergovernmental transfer funds and efficient allocation of regional expenditure play a crucial role in enhancing local government financial performance. Therefore, local governments are expected to optimize the utilization of transfer funds and improve the effectiveness and efficiency of regional expenditure to support better financial governance and strengthen public service delivery.